2011
DOI: 10.1101/gad.2027811
|View full text |Cite
|
Sign up to set email alerts
|

Foxl1-Cre-marked adult hepatic progenitors have clonogenic and bilineage differentiation potential

Abstract: Isolation of hepatic progenitor cells is a promising approach for cell replacement therapy of chronic liver disease. The winged helix transcription factor Foxl1 is a marker for progenitor cells and their descendants in the mouse liver in vivo. Here, we purify progenitor cells from Foxl1-Cre; RosaYFP mice and evaluate their proliferative and differentiation potential in vitro. Treatment of Foxl1-Cre; RosaYFP mice with a 3,5-diethoxycarbonyl-1, 4-dihydrocollidine diet led to an increase of the percentage of YFP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(170 citation statements)
references
References 33 publications
4
164
2
Order By: Relevance
“…First, by coimmunostaining for major urinary protein (MUP) or HNF4α, we confirmed that all hepatocytes activate EYFP in response to AAV8-Ttr-Cre injection ( Figure 3A and Supplemental Figure 4A). MUP is expressed only in mature hepatocytes (46), whereas HNF4α is also detectable in liver progenitor cells committed to hepatocyte differentiation (9,10). Then we excluded that AAV8-Ttr-Cre activates EYFP expression in biliary epithelial cells or liver progenitor cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, by coimmunostaining for major urinary protein (MUP) or HNF4α, we confirmed that all hepatocytes activate EYFP in response to AAV8-Ttr-Cre injection ( Figure 3A and Supplemental Figure 4A). MUP is expressed only in mature hepatocytes (46), whereas HNF4α is also detectable in liver progenitor cells committed to hepatocyte differentiation (9,10). Then we excluded that AAV8-Ttr-Cre activates EYFP expression in biliary epithelial cells or liver progenitor cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, if hepatocytes or biliary epithelial cells lose the ability to proliferate, such as in chronic injury states, liver progenitor cells are activated. Liver progenitor cells reside in or around bile ducts within periportal areas and, depending on the nature of the injury, give rise to hepatocytes or biliary epithelial cells (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the experiments with the Sox9-CreER; mTmG mice show that they arise from cells labeled for Sox9 expression at the ductal plate stage of development. These are probably small bile ducts (22,23) but the cells of origin might also be hepatoblastlike progenitor cells, thought to be in the periportal region associated with small bile ducts (26,27) or perhaps they derive from the peribiliary glands, which are associated with larger bile ducts and are reported to contain cells expressing markers characteristic of embryonic endoderm (18,19,(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is clear that progenitors arise from cells in or near the canals of Hering (the intrahepatic bile ductules in direct communication with the hepatocyte canalicular system), are likely a component of the periportal proliferation of cholangiocytes seen in response to injury (the so-called ductular reaction), and are able to repopulate injured liver, even from single-cell clones (12,13). At least some of these cells are identified by expression of the forkhead box transcription factor FoxL1 (14). Finally, while progenitor cells residing outside the liver may be capable of differentiating into hepatocyte-like cells (15,16), they are not likely to be relevant under most conditions.…”
Section: Hepatocytes Are Derived From Progenitor Cells When the Supplmentioning
confidence: 99%